Adult Talk in the Inclusive Classroom and the Socially Competent Behavior of Preschoolers With Autism Spectrum Disorder. (September 2015) - Irvin, Dwight W.; Boyd, Brian A.; Odom, Samuel L.
Difficulty with social competence is a core deficit of autism spectrum disorder (ASD). The aim of this study was to examine the link between adult talk and the socially competent behavior displayed by preschoolers with ASD concurrently and over time. A modified version of Kontos's Teacher Talk classification was used to code videos of 73 children with ASD (ages 3–5) in inclusive classrooms ( n = 33). Supporting peer relation and positive social contact forms of adult talk were concurrently associated with children's socially competent behavior. In comparison, higher amounts of supporting object play talk positively affected children's social competence over time (i.e., 1 school year), and more behavior management talk was related to worsening social competence as perceived by teachers. Implications for practice and future research are discussed.